Strengthening Halal Brand and Awareness in the Halal-Based Pharmaceutical and Cosmetic Industry in Indonesia - Minabari, Eka Safitri; Syafar Arsyad, Muh Rezky Pangeran (Universitas Syiah Kuala, 2024)
The Halal Industry is the answer to Indonesia's economic potential. This study aims to discuss the strengthening of halal brands and awareness in this halal industry, namely the halal pharmaceutical and cosmetic sectors in Indonesia. This study uses a descriptive qualitative method with a literature study where researchers collect data through discussions from books, journals, trusted websites, and other relevant research. The results of this study show that strengthening halal brands and awareness is one of the strategies in the core halal industry, the pharmaceutical and cosmetic sectors. The core halal industry has two sectors: the Halal Food and Beverage and the Halal Pharmaceutical and Cosmetic. However, this study focuses on the Halal Pharmaceutical and Cosmetic Sector, where the halal brand is an awareness for the Muslim community in Indonesia that halal products are good to use and are governed by Islamic law.